Combined effects of pre-cooling and water ingestion on thermoregulation and physical capacity during exercise in a hot environment - Hasegawa, H.; Takatori, T.; Komura,T.; Yamasaki, M. (Journal of Sports Sciences, 2006)
The aim of the present study was to determine the combined effects of pre-cooling and water ingestion on thermoregulatory responses and exercise capacity at 32°C and 80% relative humidity. Nine untrained males exercised for 60 min on a cycle ergometer at 60% maximal oxygen uptake (&Vdot;O2max) (first exercise bout) under four separate conditions: No Water intake, Pre-cooling, Water ingestion, and a combination of pre-cooling and water ingestion (Combined). To evaluate the efficacy of these conditions on exercise capacity, the participants exercised to exhaustion at 80% &Vdot;O2max (second exercise bout) following the first exercise bout. Rectal and mean skin temperatures before the first exercise bout in the Pre-cooling and Combined conditions were significantly lower than in the No Water and Water conditions. At the end of the first exercise bout, rectal temperature was lower in the Combined condition (38.5 ± 0.1°C) than in the other conditions (No Water: 39.1 ± 0.1°C; Pre-cooling: 38.7 ± 0.1°C; Water: 38.8 ± 0.1°C) (P < 0.05). Heat storage was higher following pre-cooling than when there was no pre-cooling (P < 0.05). The final rectal temperature in the second exercise bout was similar between the four conditions (39.1 ± 0.1°C). However, exercise time to exhaustion was longer (P < 0.05) in the Combined condition than in the other conditions. Total sweat loss was less following pre-cooling than when there was no pre-cooling (P < 0.001). Evaporative sweat loss in the Water and Combined conditions was greater (P < 0.01) than in the No Water and Pre-cooling conditions. Our results suggest that the combination of pre-cooling and water ingestion increases exercise endurance in a hot environment through enhanced heat storage and decreased thermoregulatory and cardiovascular strain.